(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Forensic age estimation defines an expertise in forensic medicine, which aims to define in the most accurate way to determine the unknown chronological age of the person involved in judicial or legal proceedings. Dental cementum is a vital tissue which demonstrates continuous apposition throughout the life of the tooth. Literature studies have revealed that tooth cemental annulations(TCA) would serve as a reliable tool in establishing the age of an individual. The use of specialized microscopic methods are been employed to enhance the assessment of the cemental annulations. The study aims at assessment and evaluation of cemental annulations in normal and periodontally diseased extracted teeth using phase contrast microscopic method. Methodology: A total of 60 teeth were included in the study and out of which thirty teeth were normal and 30 were periodontally involved teeth respectively. Longitudinal ground sections were prepared using micromotor and diamond disc. Sections were mounted and observed under phase contrast microscope. Measurements were made using an image analyzer software. The total width of cementum was divided by the distance between two incremental lines. The eruption age of the tooth was then added to this to obtain the chronologic age for each individual. The results of the study showed no significant deviation of estimated age from the actual age in both periodontally sound and periodontally diseased teeth. Conclusion: The study concludes that the use of phase-contrast microscopy in conjunction with image enhancement procedures improves the accuracy of age estimation and may serve as a reliable aid in forensic identification.